2011
DOI: 10.1080/02705060.2011.563513
|View full text |Cite
|
Sign up to set email alerts
|

Biological changes along the continuum of an agricultural stream: influence of a small terrestrial preserve and use of adult caddisflies in biomonitoring

Abstract: We monitored benthic macroinvertebrates and adult caddisflies along an agricultural stream continuum upstream, within, and downstream of a small forested preserve. The habitat upstream of all sites was 460% disturbed by agricultural activities. The percentage of riparian disturbance was markedly lower adjacent to the sites inside the preserve than those outside. Water physicochemical factors did not exhibit clear changes among sites, except for nitrate concentration, which was highest upstream of the preserve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 65 publications
(87 reference statements)
1
23
0
1
Order By: Relevance
“…Such concentrations accumulate naturally in larger rivers or anthropogenically in disturbed streams (Allan 2004). Michigan streams disturbed by agriculture have levels two to three times that of Fairbanks Creek (Castillo et al 2000;Houghton et al 2011a). Our low specific conductance values, as well as the lack of difference in both variables between study sites, suggested no important differences in natural or anthropogenic sediment input throughout the continuum of the stream.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Such concentrations accumulate naturally in larger rivers or anthropogenically in disturbed streams (Allan 2004). Michigan streams disturbed by agriculture have levels two to three times that of Fairbanks Creek (Castillo et al 2000;Houghton et al 2011a). Our low specific conductance values, as well as the lack of difference in both variables between study sites, suggested no important differences in natural or anthropogenic sediment input throughout the continuum of the stream.…”
Section: Discussionmentioning
confidence: 61%
“…In the case of adult caddisflies, the lack of response from the scraper functional group has been noted in previous studies (Houghton 2006(Houghton , 2007. While scraper taxonomic richness may be proportional within the Trichoptera (e.g., Wiggins 1996), scraper specimens are not abundant in blacklight samples relative to filtering collectors or shredders, or in benthic samples compared to scraper taxa of other orders (Houghton 2011a). Thus, the metric may not be abundant enough to be informative of stream conditions when using Trichoptera exclusively.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Contrarily, diversity and density of benthic communities recovered to levels in control streams without corresponding improvements in water quality. Houghton et al (2011) monitored benthic macroinvertebrates and adult caddisflies along an agricultural stream upstream, within, and downstream of a small forested preserve in Michigan. They found that the diversity of adult caddisflies was significantly higher within the preserve, with a three-fold increase in species diversity despite no clear improvements in water quality.…”
mentioning
confidence: 99%
“…Due to the importance of caddisflies in aquatic ecosystems (Mackay and Wiggins 1979) and their utility in biological water quality monitoring (Barbour et al 1999;Dohet 2002;Houghton 2007;Houghton et al 2011a), it is imperative that field samples accurately represent caddisfly populations (Figure 1). Studies of adult caddisflies usually rely on ultraviolet light traps to obtain such samples.…”
Section: Introductionmentioning
confidence: 99%